A Multilevel Analysis of Farmers’ Adoption of Water-saving Irrigation Technology: Evidence From the North China Plain - Yibei Guo; Kunpeng Zhang; Xiaohu Jia (SAGE Open)
Agricultural water scarcity poses a significant threat to food security and sustainable development. Farmers’ adoption of agricultural water-saving irrigation technologies (WSIT) is essential for addressing this challenge. However, decisions to adopt such technologies are shaped by both individual and structural factors across multiple levels. This study investigated the multilevel determinants of WSIT adoption in the North China Plain (NCP) through a field survey conducted from late 2012 to early 2013. We collected retrospective data from 818 households spanning 2010 to 2012. Initially, we employed a binomial logistic regression model to identify significant household- and village-level factors influencing WSIT adoption. Recognizing the nested nature of adoption decisions within individual and village contexts, and the importance of multilevel interactions, we further utilized a multilevel mixed-effects logistic model. Our findings indicated that household-level factors, such as farm size, access to irrigation resources, education, input costs, and village leadership, were the primary drivers of WSIT adoption. Approximately 22.7% of the variation in adoption was attributable to differences between villages. At the village level, larger village size decreased the likelihood of adoption, while the presence of Water User Associations (WUAs) had a positive influence. Mechanism analysis suggested that household-level characteristics affected farmers’ adoption behavior through possible channels such as technical training, farmers’ perception of climate change, and the availability of alternative technologies. These findings highlight the importance of considering multiple contextual factors in studying farmers’ adoption behavior and provide important policy implications for decision-makers. JEL classification: D1; Q16; Q25